1992
DOI: 10.1023/a:1018952415732
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The kinetics of the deiodination of levothyroxine in aqueous solution were studied over the pH range 1 to 12. Temperature dependence of the reaction was also studied. The log k - pH profile indicated that the kinetics of deiodination include proton attack on the anion and dianion in acidic solution and water attack on the anion and dianion in alkaline solution. A possible mechanism of the deiodination was discussed. The solid-state stability of levothyroxine sodium was studied at elevated temperatures; and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…coffee temperature) do not alter the molecular properties or stability of L-T 4 . Studies on stability, carried out with tablet formulations, have shown that sodium L-T 4 gets rapidly degraded at 60 8C (15,16). Indeed, an Italian coffee 'espresso' is served at 80-90 8C (17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…coffee temperature) do not alter the molecular properties or stability of L-T 4 . Studies on stability, carried out with tablet formulations, have shown that sodium L-T 4 gets rapidly degraded at 60 8C (15,16). Indeed, an Italian coffee 'espresso' is served at 80-90 8C (17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…At the pH of the aqueous part of the eluent (∼2.5) T 4 is quite hydrophobic [18], which enables good retention to the stationary phase upon introduction into the analytical column. In addition, the presence of an acidic buffer facilitated the formation of positive ions during ESI.…”
Section: Lc-ms/msmentioning
confidence: 99%
“…In fact, organic iodides can often undergo physical/chemical decomposition. Thyroxine, for instance, is already known to deiodinate in vitro in aqueous solution, upon UV irradiation, or in a pH‐ and temperature‐dependent manner . Thus, when assessing the metabolic stability of an iodinated pharmaceutical, it is crucial not only to analyze the carbon–iodine BDE, but also to understand how the whole molecule might interact with any metabolic pathway in vivo.…”
Section: Introductionmentioning
confidence: 99%